Emerging Evidence concerning the Role of Sirtuins in Sepsis. (8th November 2018) - Li, Lulan; Chen, Zhongqing; Fu, Weijun; Cai, Shumin; Zeng, Zhenhua
Abstract : Sepsis, a dysregulated host response to infection, is a major public health concern. Though experimental and clinical studies relating to sepsis are increasing, the mechanism of sepsis is not completely understood. To date, numerous studies have shown that sirtuins (silent mating type information regulation 2 homolog), which belong to the class III histone deacetylases, may have a varied, or even opposite, effect in the pathogenesis of sepsis. Notably, downstream mechanisms of sirtuins are not fully understood. The sirtuin family consists of sirtuins 1–7; among them, sirtuin 1 (SIRT1) is the most studied one, during the development of sepsis. Furthermore, other sirtuin members are also confirmed to be involved in the regulation of inflammatory or metabolic signaling following sepsis. In addition, sirtuins may interact with each other to form a precise regulatory mechanism in different phases of sepsis. Therefore, in this review, by accumulating data from PubMed, we intend to explain the role of sirtuin in sepsis, which we hope will pave the way for further experimental study and the potential future clinical applications of sirtuins.